Pengaruh Subtitusi Ampas Tahu pada Pakan BR2 terhadap Berat Hidup, Berat Potong, Berat Dada dan Berat Paha Ayam Broiler - Angela Lake; Charles V. Lisnahan; Theresia I. Purwantiningsih (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the effect of tofu dregs substitution in BR2 feed on live weight, cut weight, breast weight and thigh weight for broiler chickens. This research was carried out in Poultry Housing of Animal Husbandry Study Program and the Laboratory of Agriculture Faculty, Timor University during 48 days, from July until August, 2020. This research used 96 broilers that is days old chick. The experimental design used the completely randomized design (CRD) consist of four treatments and four replication. The treatment that given is: P0 (100% commercial BR2 feed), P1 (95% commercial BR2 feed + tofu waste 5%), P2 (90% commercial BR2 feed + tofu waste 10%), and P3 (85% commercial BR2 feed + tofu waste 15%). The observed variables are live weight, cut weight, percentage of cut weight, breast weight, percentage of breast weight, thigh weight and percentage of thigh weight. The results of statistical analysis show that substitution of tofu waste in BR2 feed from a level of 0.05% to a level 0,10% can increase breast weight, but had no effect on live weight, cut weight and thigh weight of broiler chickens. It was eliminated that tofu pulp can be used to replace BR2 feed by 10%.